2016
DOI: 10.1073/pnas.1515294113
|View full text |Cite
|
Sign up to set email alerts
|

Competition between anthocyanin and flavonol biosynthesis produces spatial pattern variation of floral pigments between Mimulus species

Abstract: Flower color patterns have long served as a model for developmental genetics because pigment phenotypes are visually striking, yet generally not required for plant viability, facilitating the genetic analysis of color and pattern mutants. The evolution of novel flower colors and patterns has played a key role in the adaptive radiation of flowering plants via their specialized interactions with different pollinator guilds (e.g., bees, butterflies, birds), motivating the search for allelic differences affecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 31 publications
(32 reference statements)
4
86
1
Order By: Relevance
“…The range of flavonol production was also broad (0.003 to 3.7 mg/g), with similar ranges between the pigmented (0.05‐3.7 mg/g) and white (0.003‐1.05 mg/g) species. We did not find a significant negative correlation between anthocyanidins and flavonols (Figure ) although this pattern has been observed in experimental systems …”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…The range of flavonol production was also broad (0.003 to 3.7 mg/g), with similar ranges between the pigmented (0.05‐3.7 mg/g) and white (0.003‐1.05 mg/g) species. We did not find a significant negative correlation between anthocyanidins and flavonols (Figure ) although this pattern has been observed in experimental systems …”
Section: Resultscontrasting
confidence: 54%
“…We did not find a significant negative correlation between anthocyanidins and flavonols ( Figure 3) although this pattern has been observed in experimental systems. [39][40][41] The flavonoid profiles of the white morphs of the pigmented species were similar to those of the white species, suggesting the phenotypic convergence is coupled with biochemical convergence. For two of the six polymorphic species (Table 1), the white morphs produced no detectable anthocyanidins ( Figure 2).…”
Section: Biochemical Convergence Above and Below The Species Levelmentioning
confidence: 99%
“…a,b). It should be noted that the same transformation vector, pEarleyGate 302 (Earley et al ., ), previously has been used to express pigment‐related transgenes in M. lewisii (Yuan et al ., , ), and none of the > 100 transgenic lines generated in previous studies showed a phenotype resembling the ML14257 mutant. Therefore, the current transgenic results clearly support the ‘dominant‐negative’ hypothesis.…”
Section: Resultsmentioning
confidence: 87%
“…Perhaps a more practical approach to investigate the developmental genetics of corolla tube elaboration is to employ a genetic model plant that has a corolla tube. The bumblebee‐pollinated monkeyflower species Mimulus lewisii is such a model; it has proven to be an excellent system for studying the developmental genetics of ecologically important floral traits, especially those that are difficult or infeasible to study using Arabidopsis (Yuan et al ., , , ; Sagawa et al ., ). As the first step of a systematic effort to elucidate the genetic network underlying corolla tube elaborations, we have generated several ethyl methanesulfonate (EMS) mutants of M. lewisii with altered corolla tube attributes.…”
Section: Introductionmentioning
confidence: 98%
“…Pursh (Scrophulariaceae, Lamiales), and M. cardinalis Douglas ex Benth. flowers (Chiu et al 2010, Pattanaik et al 2010, Yuan et al 2016. In Ipomea purpurea (L.) Roth (Convolvulaceae, Solanales) transposon-insertion double mutants for bHLH and MYB genes resulted in snow-white flowers where the expression of the late biosynthetic genes was completely abolished (Park et al 2007).…”
Section: Introductionmentioning
confidence: 99%